Studies on Nanocomposite Conducting Coatings. (10th July 2013) - Bhattacharyya, Amitava; Janarthanan, Gopinathan
Abstract : Nanocomposite conducting coatings can impart stable surface electrical conductivity on the substrate. In this paper, carbon nanofiber (CNF) and nanographite (NG) are dispersed in thermoplastic polyurethane matrix and coated on the surface of glass and polyethylene terephthalate (PET) film. The nanoparticles dispersion was studied under TEM. The coating thicknesses were estimated. Further, their resistance and impedance were measured. It has been observed that the 5 wt% CNF dispersed nanocomposite coatings show good conductivity. The use of NG can bring down the amount of CNF; however, NG alone has failed to show significant improvement in conductivity. The nanocomposite coating on PET film using 2.5 wt% of both CNF and NG gives frequency-independent impedance which indicates conducting network formation by the nanoparticles. The study was carried out at different test distances on nanocomposite coated PET films to observe the linearity and continuity of the conducting network, and the result shows reasonable linearity in impedance over total test length (from 0.5 cm to 4.5 cm). The impedance of nanocomposite coatings on glass is not frequency independent and also not following linear increase path with distance. This indicates that the dispersion uniformity is not maintained in the coating solution when it was coated on glass.